1976
DOI: 10.1007/bf00220238
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen dependent ciliogenesis in the chick oviduct

Abstract: Both the hormone dependency and the morphological details of estrogen-dependent ciliogenesis in the shell gland of the chick oviduct were investigated. Ciliogenesis was initiated on day 3 of estrogen treatment, and progressively more cells became differentiated until, on day 10, approximately 55% ciliation occurred with 17 beta-estradiol (1 mg/day) and approximately 75% ciliation occurred with diethylstilbestrol (1 mg/day). Simultaneous administration of progesterone with diethylstilbestrol (1 mg each/day for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Thus, consistent with previous reports of foxj1 function and the absence of cilia in the oviduct in foxj1 null mice, our findings indicate a key role for foxj1 in the ciliogenesis of the oviduct. Also considered were previous reports that indicated that estrogen signaling may be critical for ciliogenesis, thereby suggesting that E2 could activate foxj1 (Anderson & Hein 1976, Eroschenko 1982, Jansen 1984, Abe & Oikawa 1993, Comer et al 1998.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, consistent with previous reports of foxj1 function and the absence of cilia in the oviduct in foxj1 null mice, our findings indicate a key role for foxj1 in the ciliogenesis of the oviduct. Also considered were previous reports that indicated that estrogen signaling may be critical for ciliogenesis, thereby suggesting that E2 could activate foxj1 (Anderson & Hein 1976, Eroschenko 1982, Jansen 1984, Abe & Oikawa 1993, Comer et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental models have shown that oviductal development is regulated by the ovarian sex steroid hormones estrogen and progesterone (Jansen 1984). In the chick and mouse oviduct, estradiol-17 (E2) induces epithelial cell proliferation and differentiation (Anderson & Hein 1976). In this regard, the differentiation of the secretory epithelial cell phenotype to the ciliated epithelial cell phenotype can be induced by E2 in primary cultured human fallopian tube epithelial cells (Comer et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal exposure to DES induced cell proliferation and caused abnormal morphology in mouse and rat oviducts (Newbold et al 1983, Okada et al 2001. Also, in immature chicks, E2 induced cell proliferation in the oviductal epithelium (Anderson & Hein 1976). However, unlike in the uterus, the effects of E2 on the expression of AP-1 transcription factors have not been reported in the mammalian oviduct, but only in the immature chick oviduct whose c-jun and c-fos were rather reduced, with increased ovalbumin production, after E2 treatment (Cohrs et al 1988, Lau et al 1990.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ciliogenesis produced by oestrogen administration has been reported in various animals (6).…”
Section: Discussionmentioning
confidence: 99%